Caffeine inhibits adipogenesis through modulation of mitotic clonal expansion and the AKT/GSK3 pathway in 3T3-L1 adipocytes - Kim, Hyo Jung; Yoon, Bo Kyung; Park, Hyounkyoung; Seok, Jo Woon; Choi, Hyeonjin; Yu, Jung Hwan; Choi, Yoonjeong; Song, Su Jin; Kim, Ara; Kim, Jae-woo (BMB reports, 2016)
Caffeine has been proposed to have several beneficial effects on obesity and its related metabolic diseases; however, how caffeine affects adipocyte differentiation has not been elucidated. In this study, we demonstrated that caffeine suppressed 3T3-L1 adipocyte differentiation and inhibited the expression of CCAAT/enhancer binding protein (C/EBP)α and peroxisome proliferator-activated receptor (PPAR)γ, two main adipogenic transcription factors. Anti-adipogenic markers, such as preadipocyte secreted factor (Pref)-1 and Krüppel-like factor 2, remained to be expressed in the presence of caffeine. Furthermore, 3T3-L1 cells failed to undergo typical mitotic clonal expansion in the presence of caffeine. Investigation of hormonal signaling revealed that caffeine inhibited the activation of AKT and glycogen synthase kinase (GSK) 3 in a dose-dependent manner, but not extracellular signal-regulated kinase (ERK). Our data show that caffeine is an anti-adipogenic bioactive compound involved in the modulation of mitotic clonal expansion during adipocyte differentiation through the AKT/GSK3 pathway. [BMB Reports 2016; 49(2): 111-115].